Foundational Skills : Phonics for First Grade. - Education, Shell (Foundational Skills: Phonics Ser., 2013)
Support students' phonetic development as they practice key first grade phonics skills. Focus on phonics with fun and engaging activity pages that are research based and support the Common Core State Standards.